THE IMPACT OF BRAND EQUITY ELEMENTS ON THE REPURCHASE INTENTION OF XIAOMI SMARTPHONE IN XIAOMI USERS SMARTPHONE (RESEARCH ON STUDENTS OF UNIVERSITAS BRAWIJAYA, MALANG) - FREDY TRIYAN SEPTIANUS (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
The Aim of this study is to examine the influence of Brand Equity elements (Brand Awareness, BrandAssociation, Perceived Quality and Brand Loyalty) on Repurchase Intention of Xiaomi Smartphone on CollegeStudent in Brawijaya University Malang as Scope. The Research is Explanatory Research which explains the casualrelation between the variables through hypothesis testing. The data collection technique of this study usesquestionnaires. This study used 120 samples of the student who ever used Xiaomi Smartphone. The research timewas held in February 2019. The sampling technique used purposive sampling and the research instruments weretested using the Validity Test, Reliability Test. The hypothesis used Partial (t-Test) using Partial Linear Square(PLS) analysis technique to analyze the data. The result from this study showed that variable of brand awareness,brand association, perceived quality and brand loyalty provides good value and each of them made a significanteffect on Repurchase Intention.Keywords: Brand Equity, Brand Awareness, Brand Association, Perceived Quality, Brand Loyalty and RepurchaseIntention.